2009
DOI: 10.1007/s00380-008-1123-0
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-2 enhances the cytotoxic activity of circulating natural killer cells in patients with chronic heart failure

Abstract: Our objective was to investigate the effect of interleukin-2 (IL-2) on the cytotoxic activity of natural killer (NK) cells in patients with chronic heart failure (CHF). Natural killer cells were isolated from 48 patients with CHF and 30 healthy subjects. The cytotoxic activities of the NK cells were assessed with the thiazolyl blue tetrazolium bromide (MTT) approach. Interleukin-2 (20 ng/ml) was added to the cell culture to stimulate the cytotoxicity of the NK cells. The cell number in the New York Heart Assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…Beside changes in B‐cell populations, NK cells were distinctively reduced in CHF patients compared with age‐matched controls in our study, as reported previously . NK cells from patients with heart failure were shown to have impaired cytotoxic functions, and increased regulatory T‐helper cells suppress the cytotoxic function of NK cells in heart failure patients .…”
Section: Discussionsupporting
confidence: 88%
“…Beside changes in B‐cell populations, NK cells were distinctively reduced in CHF patients compared with age‐matched controls in our study, as reported previously . NK cells from patients with heart failure were shown to have impaired cytotoxic functions, and increased regulatory T‐helper cells suppress the cytotoxic function of NK cells in heart failure patients .…”
Section: Discussionsupporting
confidence: 88%
“…In the immune system, NK cell activity is thought to be one of the important indices for monitoring immunity because innate immunity is the first line of defense against infections. It has been shown that NK cell activity is impaired due to various stressors, such as chronic heart failure (40) and high-intensity physical exercise. (41) Moreover, it has been understood that NK cell activity is mediated, at least partially, by nitric oxide-mediated pathways.…”
Section: Discussionmentioning
confidence: 99%